MODELTEAM GAME TOURNAMENT (TGT) BERBANTUAN MEDIA KARTU SOAL BERBASIS HOTS TERHADAP HASIL BELAJAR MAHASISWA - PANDA, FLORENTINA. M; DJARWO, CATUR F. (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2021)
The atomic structure material has certain characteristics and difficulties, including the need for a lot of knowledge and analytical skills that students have. Therefore, students need to be given the right learning model in order to increase their interest and learning activities.The learning model that can be done is to carry out learning by applying a cooperative approach, one of which is the Team Game Tournament (TGT) type. The effectiveness of using the TGT model can be increased by providing question cards media. The question card media used in this study is a card containing Higher Order Thinking Skill (HOTS) questions that require students' higher order thinking skills.The purpose of this study was to determine the effectiveness of using the TGT type cooperative learning model with the help of HOTS-based question card media on atomic structure material on higher-order thinking skills and student learning outcomes of physics education.Based on the results of research and calculations, it can be concluded that the provision of question card media in the TGT model on the atomic structure material is effective on student learning outcomes with Sig values. (0.028) <0.05, then there is a difference in learning outcomes so that it can be concluded that the experimental class is more effective than the control class. Supported by the highest lowest scores in the experimental group, namely 75 and 100 with an average of 90.02, while the control group was 65 and 100 with an average of 84.2.